Citizens' views on electricity use, savings and production from renewable energy sources: A case study from a Greek island. (November 2017) - Tampakis, Stilianos; Arabatzis, Garyfallos; Tsantopoulos, Georgios; Rerras, Ioannis
Abstract: A country's economic growth is closely linked to the availability, generation, distribution and use of energy. At the same time, the increased rate of global energy consumption is a risk to development and to the efforts to safeguard people's living standards for the future. The production of electricity from RES substantially contributes to the energy security of states and to environmental protection. Greece has a valuable and exploitable potential in several RES and can significantly increase their use. However, various significant institutional changes have taken place in Greece over the last decades involving changes to the energy mix, the penetration of RES and attracting foreign investment. The present research took place on the island of Andros, Greece, with the help of a questionnaire and face-to-face interviews. It is noted that the respondents agree with the need to save energy and to expand the use of green energy. They say they are slightly satisfied by the messages given through the Mass Media. They have insufficient information regarding RES systems that can be used in households and believe that a major subsidy from the state would lead to their purchase.